Framework Index security information to support evaluation, adoption and improvement of methods in developing variables - Faiz, M. Kaffah; Slamet, Cepy; Aedah, Abd Rahman; Khaerul, Manaf; Beki, Subaeki (2019)
The governance of information security in the Indonesian Government has not been completely improved. Many related variables components are not measured. This study aims to observe an evaluation for application of information security index framework in Indonesian government institutions as the implementation of electronic government. The analysis is carried out by adopting an information security index framework produced in the rank of e-government. The study uses a triangulation approach within a mixed method. This study results in a novel adoption model of information security index framework equipped by two new variables. Therefore, a proper policy of the Indonesian government is required for its implementation.